Treatment with Argovit® Silver Nanoparticles Induces Differentiated Postharvest Biosynthesis of Compounds with Pharmaceutical Interest in Carrot (Daucus carota L.); Nanomaterials; Vol. 11, iss. 11 - Santoscoy-Berber L. S. Laura Sofia; Antunes-Ricardo M. Marilena; Gallegos-Granados M. Z. Melissa Zulahi; Garcia-Ramos Ju. C. Juan Carlos; Pestryakov A. N. Aleksey Nikolaevich; Toledano-Magana Ya. Yanis; Bogdanchikova N. Nina; Chavez-Santoscoy R. A. Rocio Alejandra (2021, 2021)
Title screen